Одержання гідрощільних виливків із синтетичного сірого та високоміцного чавуну за моделями, що газифікуються - Терещенко, М.Я.; Калюжний, П.Б.; Кротюк, С.О. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to scientific and practical research of synthetic iron melting and production of impermeability castings by lost-foam casting. The use of synthetic iron from an economic point of view is more advantageous, in addition, it is characterized by higher mechanical and special properties, such as tightness. Theoretical analysis shows that the type of metal matrix structure, shape and size of graphite inclusions are significantly influenced on the tightness of the cast iron. In the article the questions of melting high quality synthetic iron in induction furnaces are considered, in particular, the basic requirements for carburizers and charge materials are substantiated. It is determined that the content of ash and sulfur in the carburizer should not exceed 0.1 %, and the best degree of assimilation in induction furnaces has a carburizer with a particle size of 1.0–5.0 mm. The order of charge loading into an induction crucible furnace for melting of synthetic cast iron is presented and substantiated. Practical aspects and peculiarities of casting production from synthetic cast iron by lost-foam casting are described, including processes of melt modification and temperature modes of its pouring, production of polystyrene foam models, choice of gating systems and chemical composition of alloys. A microstructural analysis of cast iron castings was performed, which showed that gray and high ductile iron had a pearlitic and ferrite-pearlitic structure, respectively, with small graphite inclusions of up to 5 %. As a result of mechanical tests, it is determined that the synthetic cast iron obtained corresponds to the grades GJL-300 and GJS-450-5. Shell castings made of these grades of cast iron with a wall thickness of 5–8 mm during the test withstood a fluid pressure of 40 MPa. The discrepancy between the conditions of impermeability was observed only in castings with foundry defects. The results of the works can be used at foundry enterprises to optimize the manufacturing processes of cast iron castings hydraulic equipment, shut-off valves and other impermeability products.